2018
DOI: 10.3389/fmicb.2018.03078
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Mono-O-Glucosylation of Ras Subtype GTPases Between Toxin A and Toxin B From Clostridioides difficile Strain 10463 and Lethal Toxin From Clostridium sordellii Strain 6018

Abstract: Clostridioides difficile toxin A (TcdA) and Toxin B (TcdB) trigger inflammasome activation with caspase-1 activation in cultured cells, which in turn induce the release of IL-6, IFN-γ, and IL-8. Release of these proinflammatory responses is positively regulated by Ras-GTPases, which leads to the hypothesis that Ras glucosylation by glucosylating toxins results in (at least) reduced proinflammatory responses. Against this background, data on toxin-catalyzed Ras glucosylation are required to estimate of pro-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…There is currently no standard nomination for TcdB variants, miscellaneous names referred to same toxin variants were sometimes assigned in different studies. For example, TcdB variant initially identified from NAP1/BI/027 strains was later called TcdB 027 28,29 , TcdB HV 22,30 , TcdB NAP1 15 , TcdB2 31 , TcdB R20291 32,33 , or TcdB-R20291 34 . In 2005, Rupnik et al 35 proposed nomenclature of C. difficile toxin variants by adding the bacterial strain in which the toxin was originally found.…”
Section: Discussionmentioning
confidence: 99%
“…There is currently no standard nomination for TcdB variants, miscellaneous names referred to same toxin variants were sometimes assigned in different studies. For example, TcdB variant initially identified from NAP1/BI/027 strains was later called TcdB 027 28,29 , TcdB HV 22,30 , TcdB NAP1 15 , TcdB2 31 , TcdB R20291 32,33 , or TcdB-R20291 34 . In 2005, Rupnik et al 35 proposed nomenclature of C. difficile toxin variants by adding the bacterial strain in which the toxin was originally found.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we cannot exclude the involvement of additional mechanisms to modulate the activity of Rac1 in the present study, considering that specific modification at a single threonine residue in the small GTPases leads these important key players of several signaling pathways to their functional inactivation. TcdA and TcdB glucosylate Rac1/Cdc42 at threonine-35 and RhoA, decreasing their active levels into the cells ( Halabi-Cabezon et al, 2008 ; Schoentaube et al, 2009 ; Genth et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, whereas TcdB has been shown to inhibit the activity of the Wnt/β-catenin signaling pathway by binding to the FZD-7 receptor expressed by cells in the colonic epithelium ( Tao et al, 2016 ), thereby preventing its activation by Wnt3a, TcdA has not shown affinity for FZD2, FZD3, or FZD-7 ( Gupta et al, 2017 ). Like TcdA, TcdB induces inactivation of Rho GTPases including Rac-1 ( Halabi-Cabezon et al, 2008 ; Schoentaube et al, 2009 ; Genth et al, 2018 ), which should cause Wnt/β-catenin signaling pathway inhibition. However, the investigation on TcdB effect in this pathway was not the aim of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 134 (for tryptic digestion) and 96 (for chymotryptic digestion) transitions from eight small GTPases were monitored in two scheduled LC–MRM runs (Junemann et al, 2017). Together, the substrate profiles of the three LCTs (TcdA, TcdB, and TcsL) in Caco‐2 cells were interrogated, and it was found that (H‐/K‐/N‐)Ras and Rap(1/2) could be glucosylated by TcsL and TcdA, but not TcdB (Genth et al, 2018).…”
Section: Proteomic Studies Of Gtp‐binding Proteinsmentioning
confidence: 99%